1991
DOI: 10.3382/ps.0702028
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interactions Using Fast-Growing, Lean or Fat Broiler Chickens, Originating from The Netherlands and Israel, Raised at Normal or Low Temperature

Abstract: Male and female broiler chicks from five different broiler crosses (WI = Israeli chicks selected for body weight; LF and HF = Israeli chicks selected for low and high abdominal fat, respectively; FC = Dutch chicks selected for feed conversion; and WN = Dutch chicks selected for body weight) were raised under normal and subnormal temperatures. Weight gain, protein and fat content in the carcass, and feed and protein efficiency were determined at 4 and 6 wk of age, and at equal body weight. In addition to an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
2
13
0
2
Order By: Relevance
“…Chickens, diets, housing, and measurements have been described by Leenstra and Cahaner (1991). They reported on the comparisons between normal and suboptimal temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chickens, diets, housing, and measurements have been described by Leenstra and Cahaner (1991). They reported on the comparisons between normal and suboptimal temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In three other rooms, normal temperatures, i.e., gradually decreasing from 33 C at hatch to 20 C at 6 wk of age (Leenstra and Cahaner, 1991), were applied. Relative humidity was kept at 60% for both temperature schemes.…”
Section: Climatementioning
confidence: 99%
“…Outbred broilers of the R line and the FC line from ID-Lelystad (formerly COVP-Het Spelderholt) (Leenstra & Cahaner, 1991) and from one commercial line (Ross), purchased from the Spelderholt Institute for Poultry Reseach, The Netherlands (called the C line), were used. The R and FC lines are experimental lines developed from common ancestors, with the R line selected solely on the basis of growth rate and the FC line solely on feed conversion efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…No significant interaction of temperature and diet was observed, therefore, only the main effects for temperatures and dietary treatments are presented. Austic (1985), Leenstra and Cahaner (1991) and Borges at al. (2004) reported that broilers kept in high ambient temperature produce less absolute carcass weight, and this decrease is particularly evident in breast meat (Howlider and Rose, 1989).…”
Section: Resultsmentioning
confidence: 97%